1942
DOI: 10.1021/j150422a021
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of Gases on the Surface of a Single Crystal of Copper. I. Oxygen.

Abstract: Many important processes, such as corrosion, contact catalysis, and powder metallurgy, depend in varying degrees on the reaction of gases on the surface of metals. The object of this investigation is to study the mechanism of this type of reaction on single crystals of copper. In this paper (Part I) experiments are described which show that the rate of reaction with oxygen varies greatly with the crystal plane along which the surface is prepared. In Part II experiments will be described which show that catalyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1951
1951
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…It is well-known that a graphene coating can change the Cu oxidation behavior, and this effect is widely used to optically characterize graphene coverage and defects. , The optical contrast and color can thereby be linked to the Cu oxide thickness, ranging from metallic white (unoxidized) to yellow, orange, and red with increasing thickness of the Cu oxide. We verify the correlation between optical contrast and degree of Cu oxidation via a combination of X-ray photoelectron spectroscopy (XPS) microscopy, Raman spectroscopy, and AFM. For XPS analysis, the sample was annealed at 100 °C in vacuum to remove surface contamination.…”
Section: Resultsmentioning
confidence: 90%
“…It is well-known that a graphene coating can change the Cu oxidation behavior, and this effect is widely used to optically characterize graphene coverage and defects. , The optical contrast and color can thereby be linked to the Cu oxide thickness, ranging from metallic white (unoxidized) to yellow, orange, and red with increasing thickness of the Cu oxide. We verify the correlation between optical contrast and degree of Cu oxidation via a combination of X-ray photoelectron spectroscopy (XPS) microscopy, Raman spectroscopy, and AFM. For XPS analysis, the sample was annealed at 100 °C in vacuum to remove surface contamination.…”
Section: Resultsmentioning
confidence: 90%
“…At the oxygen pressure, temperature and exposure times used in these studies, only cuprous oxide is expected to form 39,225,226 . We review studies showing that the growth of cuprous oxide on low-index copper surfaces is epitaxial with the substrate 14,[227][228][229][230] , through nucleation and coalescence of nanoislands 113,114,202,203,227,231,232 (as schematically represented in Fig. 6).…”
Section: Oxide Film Growthmentioning
confidence: 99%
“…Clean copper surfaces have been found to oxidize at different rates, with the Cu(100) face reported to have the fastest rate of oxidation, at odds with the oxidation rates measured for the formation and growth of oxide nano-islands. Indeed, Young 228 et al and Gwathmey 229 et al found that the order of oxidation rate for the low-index surfaces is (100), (111), (110) with (100) the fastest oxidising facet, for a wide range of temperatures. Rhodin 274 found instead the order to be (100), ( 110), (111) with (100).…”
Section: Long-term Copper Oxidationmentioning
confidence: 99%
“…This paper presents the results of a study of the surface-structure sensitivity of the initial oxidation of Cu( hkl ) surfaces. The oxidation of Cu single crystals, specifically Cu(111), has been studied experimentally and with theory , for decades. Scanning tunneling microscopy (STM) studies by Matsumoto et al showed that upon room-temperature exposure to O 2 , step edges on the Cu(111) surface were faceted into three directions that were aligned with the close-packed directions of the Cu(111) terrace .…”
Section: Introductionmentioning
confidence: 99%